Assessing the influence of real releases on explosions: Selected results from large-scale experiments. (September 2021) - Hisken, Helene; Mauri, Lorenzo; Atanga, Gordon; Lucas, Melodia; van Wingerden, Kees; Skjold, Trygve; Quillatre, Pierre; Dutertre, Antoine; Marteau, Thibault; Pekalski, Andrzej; Jenney, Lorraine; Allason, Dan; et al.
Abstract: The research activities in the project Assessing the Influence of Real Releases on Explosions (AIRRE) included a unique series of large-scale explosion experiments with high-momentum jet releases directed into congested geometries with subsequent ignition. The primary objective for the AIRRE project was to gain improved understanding of the effect that realistic releases and turbulent flow conditions have on the consequences of accidental gas explosions in the petroleum industry. A secondary objective was to develop a methodology that can facilitate safe and optimal design of process facilities. This paper presents selected results from experiments involving ignition of a highly turbulent gas cloud, generated by a large-scale, pressurised release of natural gas. The paper gives an overview of the effect on maximum explosion overpressures of varying the ignition position relative to the release point of the jet and a congested region placed inside the flammable cloud, with either a high or a medium level of congestion. For two of the tests, involving a jet release and the medium congestion rig, the maximum overpressures significantly exceeded those obtained in a quiescent reference test. The paper presents detailed results for selected tests and discusses the effect of the initial flow field generated by realistic releases – including turbulence, net flow and concentration gradients – on relevant explosion phenomena. Highlights: 15 large-scale tests with ignited high-momentum jet releases performed. Delayed ignition of natural gas jets with mass flow in excess of 100 kg/s. Jets either directed into two different congested geometries or into open area. Explosions of realistic releases more severe than quiescent reference case.